Optimalisasi Peran DPRD dalam Pembentukan Peraturan Daerah di Kabupaten Tanjung Jabung Barat - Satoso, Sukamto; Hartati, Hartati; Helmi, Helmi (Universitas Batanghari Jambi, 2024)
Indonesia has thousands of regulations issued by both the central government and regional governments. Regional regulations were born from the design of regional autonomy which was formed based on the freedom and independence of regions to manage their own households. The essence of the formation of regional regulations is aimed at providing protection and welfare for the community. However, it cannot be denied that there are still many regional regulations that are problematic both in terms of quality and quantity. One of the reasons why many regional regulations are problematic is that regional governments and DPRD are less than optimal in carrying out the legislative functions attached to them. So, to solve this problem, it is necessary to optimize the role of the DPRD in forming regional regulations. This research is empirical juridical research that uses a descriptive approach. The population and sample for this research is the DPRD of West Tanjung Jabung Regency. The purpose of this research is to provide an understanding of the implications of Law Number 13 of 2022 concerning Regulations for the Formation of Legislation on existing Regional Regulations as well as understanding the formation of Regional Regulations using the omnibus law method and it is hoped that this can become evaluation material for the government to overcome the problem of too many regulations (overregulated), overlapping (overlapping). The results of this research are that in an effort to overcome a number of problematic regional regulations, the omnibus law method is a new breakthrough in structuring regional regulations. Structuring regional regulations using the omnibus law method will be more effective and efficient in simplifying the formation of regional regulations and development, producing quality regional regulations and making the implementation of regulations more effective.